2015
DOI: 10.1002/2015jc010884
|View full text |Cite
|
Sign up to set email alerts
|

Observational validation of the diffusive convection flux laws in the Amundsen Basin, Arctic Ocean

Abstract: The low levels of mechanically driven mixing in many regions of the Arctic Ocean make double diffusive convection virtually the only mechanism for moving heat up from the core of Atlantic Water towards the surface. In an attempt to quantify double diffusive heat fluxes in the Arctic Ocean, a temperature microstructure experiment was performed as a part of the North Pole Environmental Observatory (NPEO) 2013 field season from the drifting ice station Barneo located in the Amundsen Basin near the Lomonosov Ridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 40 publications
6
42
2
Order By: Relevance
“…This is likely to occur also for double diffusion at high enough Ra and may well be the case in some of the thicker diffusive layers in the Arctic Ocean. In fact, Guthrie et al (2015) found a decent agreement between observed fluxes and fluxes calculated using the 1 /3 exponent, although the agreement was even better with a 0.29 exponent. More research is needed before we can propose an accurate flux law for diffusive convection that applies to all ocean and lake environments.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…This is likely to occur also for double diffusion at high enough Ra and may well be the case in some of the thicker diffusive layers in the Arctic Ocean. In fact, Guthrie et al (2015) found a decent agreement between observed fluxes and fluxes calculated using the 1 /3 exponent, although the agreement was even better with a 0.29 exponent. More research is needed before we can propose an accurate flux law for diffusive convection that applies to all ocean and lake environments.…”
Section: Discussionmentioning
confidence: 79%
“…Both these studies support a downward revision of the commonly used Rayleigh number exponent of 1 /3. However, the two studies support rather different revised exponents, 0.2 in the case of Sommer et al (2013) and 0.29 in the case of Guthrie et al (2015), 1 and there is a large scatter of points in both studies. The Rayleigh numbers are generally larger in the Amundsen Basin than in Lake Kivu with a mean value of 10 9 compared to 2.4 3 10 8 for the latter location, but there is a large spread within each staircase and Rayleigh numbers vary between about 10 5 and 10 10 at both locations.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations